(untitled) (Acta Entomologica Serbica, 2021)
The painted maple aphid, Drepanaphis acerifoliae (Thomas, 1878), is present on Acer saccharinum L. (silver maple) in Serbia. It was found for the first time in 2019 in parks in Novi Sad, and in 2020 it was registered in Belgrade. It is a North American species that has been extending its distribution in Europe since 1992. Serbia is the fourth European country in which it has been found, following Italy, Spain and Hungary. Drepanaphis acerifoliae was found to be present on all examined A. saccharinum L. trees where it is usually very numerous. It was not found on A. platanoides L., A. campestre L., A. pseudoplatanus L. or A. negundo L. The morphology of viviparous parthenogenetic females, oviparous females and males is presented, with original drawings and photos.